Factor affecting online purchase behavior - Hasan, Hamisah; A. Rahim, Samsudin (School of Media and Communication Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2008)
The study examined the relationship between consumer personality and cultural dimensions to that of purchasing behavior through cyber advertising. Krugman’s Low Involvement theory and Hofstede’s Cultural Dimensions were incorporated in the study. A survey was conducted in the Subang Jaya, Puchong and Kuala Lumpur area. The sample consisted of 504 respondents drawn from a simple random sampling. Spearman Correlation Coefficients was used to analyze the data. The study showed as suggested by Krugman’s Low Involvement theory, high involvement products and attitude towards Internet contributed significantly to the purchasing behavior through cyber advertising. Thus indicating the Internet to be better suited for high involvement products and services as well as help increase the tendency to purchase products and services online. Similarly, the study also showed that the convenience dimension of the consumer personality variable formed a significant relationship with purchasing behavior through cyber advertising. Although Hofstede’s Cultural Dimensions argued that cultural dimensions influences the adoption of innovations, yet results obtained from the study failed to support the theory as it was found that risk personality which represent the other dimension of the consumer personality and the cultural dimensions failed to support the hypotheses as observed in the non-significant relationships between the variables and the purchasing behavior through cyber advertising.